The methods of translation phraseologisms in the process of cross-cultural communication - Бейсембaев Б. Ш.; Aхметбек Г. (Journal of Oriental Studies, 2017)
This article describes communication between the culture and the translation, also discusses specific translation methods of phraseologisms in cross-cultural communication process. In order to translate specific text one must deeply understand cultural meaning of the text, and according to the context use various translation methods. This paper provides analysis and certain translation methods. These methods contribute to the improvement of translation quality and accuracy of the interpretation, which effectively aids in cultural exchange.